Occupational safety in a frictional labor market - Martin Kerndler (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2022)
This paper studies the provision of occupational safety when the labor market is subject to search frictions. While safety measures are costly for firms, they reduce workers' mortality. We show that the presence of search frictions decreases the socially optimal level of occupational safety relative to a frictionless labor market, leading to excess mortality. In a decentralized setting where wages and safety measures are bargained at the firm level, matching externalities and a labor supply externality may further reduce safety provision. We obtain conditions under which these externalities are internalized by firms and workers, and discuss the role of policy for promoting occupational safety. Calibrating the model to the US, we find that search frictions explain 8%-14% of the work-related mortality rate, which indirectly makes them the third largest cause of work-related death.
Keywords: J17; J28; J32; J38; J64; 330; occupational safety; mortality; search frictions; Nash bargaining